Application of the detailed balance model to thermoradiative cells based on a p-type two-dimensional indium selenide semiconductor - Muhammad Yusrul Hanna; Ahmad Ridwan Tresna Nugraha; Muhammad Aziz Majidi (SINERGI, 2022)
Thermoradiative (TR) cells are energy conversion devices that convert low-temperature waste heat to electricity. TR cells work on the same principles as photovoltaics, but they produce a reverse bias voltage due to higher cell temperature than the environment temperature. Depending on the energy gap of the material, temperature difference would generate electrical energy by electron-hole pair recombination. In this work, we propose a two-dimensional (2D) InSe for applications in the TR cells. The electronic properties of 2D InSe are obtained by using first-principles calculations. Then, the calculated energy gap is used to estimate output power density and efficiency according to the Shockley-Queisser framework through a detailed balance model adapted with the TR cells. Using a heat source at  = 1000 K and the ambient temperature = 300 K, an ideal TR cell of 2D InSe at the maximum power point can achieve output power density and efficiency up to 0.061 W/m2 and 4.41%, respectively, with an energy gap of 1.43 eV. However, sub-bandgap and non-radiative losses will degenerate the cell's performance significantly.